Enhancing Labor Mobility in ASEAN: Focus on Lower-skilled Workers - Aniceto Jr. C. Orbeta (Philippine Institute for Development Studies (PIDS), 2013)
It is clear from data that worker movements in the Association of Southeast Asian Nations (ASEAN), like elsewhere, are dominated by unskilled and semiskilled workers. It is also well-known that movements of these types of workers are dominated by irregular migration mainly because of lack of avenues for legal migration for them (Abella 2006). Yet discussions either globally (within and outside GATS) and regionally such as under AFAS/AEC are all focused on professionals and highly skilled workers. This attitude continues even if both back-of-the-envelope and systematic calculations using general equilibrium models show that movements of workers, in general, and lower-skilled workers, in particular, are beneficial not only for sending but for host country citizens as well (Walmsley et al. 2007).The paper provides recommendations based on known initiatives/measures to facilitate freer labor movements in ASEAN. The focus is lower-skilled workers because existing discussion such as the ASEAN Economic Community (AEC) Blueprint does not yet cover them. To achieve this, the paper provides a description of (a) the policy and institutional arrangements, both at the national and regional level, that currently govern the cross-country labor movement within ASEAN for both skilled and unskilled workers; and (b) the analytical framework that supports the discussions in deriving the recommendations. The paper also pointed out that not only can existing arrangements be extended to cover lower-skilled workers but also that there are already experiences on these types of worker movements.
Keywords: F22; J61; 330; labor migration; ASEAN; Philippines; unskilled workers